Ultrasound and magnetic resonance imaging evaluation of the femoral and sciatic nerves. A study of healthy volunteers - Rusu, Georgeta Mihaela (Med Pharm Rep, 2020)
BACKGROUND AND AIMS: The study describes the femoral (FN) and sciatic nerves (SN), explored using ultrasound (US) and magnetic resonance imaging (MRI). The aims of the study are: to establish US/MRI correlations and define reference values: for the anteroposterior (AP) and mediolateral (ML) diameters and cross-sectional area (CSA) of the two nerves respectively, in well-defined anatomical measuring sites; to analyze the intraobserver variation; to define the value with least variability; to determine differences between the right-left and male-female reference values. METHODS: A prospective study was carried out on 24 healthy volunteers (11 men and 13 women). MRI scans were performed using a 1.5T system. To visualize both nerves (FN and SN), a single 3D T2 weighted acquisition was performed, in the coronal plane, with a wide FOV. For ultrasonographic examinations, a Hitachi EUB-8500 ultrasound machine, equipped with a 13 MHz linear transducer was used. The measurements were performed at well-defined anatomical locations. The mean reference values of the AP, ML diameters and CSA were calculated for femoral and sciatic nerves, both on MRI and US. The correlations between the values determined by the two techniques were analyzed. The intra-observer variation was calculated by measuring the nerves at the same anatomical location at two separate time points. RESULTS: Wilcoxon matched-pairs signed rank test indicated a non-significant difference (p> 0.05) for the femoral and sciatic nerves, on both sides, except the femoral nerve ML diameter on MRI (p=0.014). The mean MRI and US reference values for the femoral nerve were calculated between the psoas and iliac muscles: FNAPMRI 4.533 ± 0.486, FNAPUS 4.800 ± 1.237, FNMLMRI 6.172 ± 1.203, FNMLUS 7.685 ± 3.338, FNCSAMRI 24.811 ± 3.394, FNCSAUS 26.285 ± 17.608. The mean MRI and US measurements for the sciatic nerve were determined under the buttock, at the level of the ischial tuberosity: SNAPMRI 5.500 ± 1.201, SNAPUS 5.975 ± 1.312, SNMLMRI 10.375 ± 2.272, SNMLUS 13.500 ± 1.661, SNCSAMRI 50.625 ± 15.373, SNCSAUS 53.631 ± 15.847. The MRI and US differences between right and left sides, both for the femoral and sciatic nerves were insignificant. In selected cases, Wilcoxon paired test indicated differences between subjects, according to their gender, both on MRI and US. CONCLUSION: Reference values for the femoral and sciatic nerves at specific anatomical sites were identified. Side to side variation and gender related differences add to current knowledge on nerve size in young Caucasian population.